2017
DOI: 10.18632/oncotarget.15347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variability in high throughput screening data: applications to melanoma cell lines and drug responses

Abstract: High-throughput screening (HTS) strategies and protocols have undergone significant development in the last decade. It is now possible to screen hundreds of thousands of compounds, each exploring multiple biological phenotypes and parameters, against various cell lines or model systems in a single setting. However, given the vast amount of data such studies generate, the fact that they use multiple reagents, and are often technician-intensive, questions have been raised about the variability, reliability and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…In the current study, we describe a number of biological (cell type, medium composition and volume, and seeding density) and technical (edge effect, drug type, dose, storage, and treatment time, assay duration time, dose-response metric) factors that should be taken into consideration to achieve more reliable and reproducible drug-dose sensitivity screens in 2D models. Although many of these factors are known to affect drug response, few studies have proposed strategies to quantify and correct sources of experimental variability in cell-based drug screens using QCM [6][7][8]16,18,19,32 . The optimization strategy used here can be adapted to other cell-based and animal model systems by first identifying confounding factors in the experimental setup, followed by optimization of critical experimental parameters and assessment of data quality.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we describe a number of biological (cell type, medium composition and volume, and seeding density) and technical (edge effect, drug type, dose, storage, and treatment time, assay duration time, dose-response metric) factors that should be taken into consideration to achieve more reliable and reproducible drug-dose sensitivity screens in 2D models. Although many of these factors are known to affect drug response, few studies have proposed strategies to quantify and correct sources of experimental variability in cell-based drug screens using QCM [6][7][8]16,18,19,32 . The optimization strategy used here can be adapted to other cell-based and animal model systems by first identifying confounding factors in the experimental setup, followed by optimization of critical experimental parameters and assessment of data quality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the SK-MEL-2 cell line was received directly from Memorial Sloan Kettering Cancer Center through the Cancer Cell Line Encyclopedia (CCLE) repository and MeWo cell line from the Developmental Therapeutics Program's NCI-60 repository. The Translational Genomics Research Institute (TGen) had access to all other UACC-cell lines through the UACC [ 14 ]. All cell lines were of low passage number.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in protocols used, the media within which the cells are suspended, the precise formulation of the drugs used in the screening, the origins of the cell lines used, among other items, can create differences in outcome of studies involving what are thought to be the same cell lines. It is arguable that many of these technical sources of variation in cell line-based HTS studies can be identified and possibly controlled for in well-designed experiments [ 14 ]. However, the analytical methods used to draw inferences about the relationship between a subset of cell lines’ observed dose-dependent responses to a drug and characteristics of those cell lines (e.g., their genomic, transcriptomic, or proteomic profiles) also play an important (and often overlooked) role in the identification of factors that might mitigate a tumor's response to a drug.…”
Section: Introductionmentioning
confidence: 99%
“…De fato, diversas plataformas para triagem de compostos estão descritas na literatura, inclusive no contexto de melanoma. O uso de triagem em larga escala, do inglês High Throughput Screening -HTS, se destaca na quantidade e velocidade de aquisição de dados, como exemplificado no ensaio de responsividade de 30 linhagens de melanoma a 120 candidatos a fármacos (Ding et al, 2017).…”
Section: Modelos De Cultura Celular Como Ferramentas Para Estudos In unclassified